2016
DOI: 10.1002/ece3.2584
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and humoral immunity in a wild mammal: Variation with age & sex and association with overwinter survival

Abstract: Immune defenses are expected to be crucial for survival under the considerable parasite pressures experienced by wild animals. However, our understanding of the association between immunity and fitness in nature remains limited due to both the complexity of the vertebrate immune system and the often‐limited availability of immune reagents in nonmodel organisms. Here, we use methods and reagents developed by veterinary researchers for domestic ungulates on blood samples collected from a wild Soay sheep populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 54 publications
4
38
2
Order By: Relevance
“…We found the effects of sex and/or reproductive allocation on spring FEC became more apparent in adults compared to juveniles and yearlings: juvenile FEC was not influenced by sex or reproductive status; there was marginal evidence that yearling FEC was influenced by sex; and adult FEC was influenced by both. Juveniles had generally high FEC, as predicted from previous research on other wild vertebrates (Wilson et al 1996;Isomursu et al 2006;Hayward 2013;Watson et al 2016) and humans (Simon et al 2015), which suggests that juveniles have not developed fully effective immune defences. Yearling males tended to have higher spring FEC than females (marginal statistical support; estimate = 0.36 AE 0.17 SE, DAIC = À1; evidence ratio = 0.63); this result is consistent with studies from diverse species that have found males to have less effective immune responses (Tschirren et al 2003;Hayward 2013;Klein & Flanagan 2016;Watson et al 2016).…”
Section: Reproductive Allocation Influences Fecsupporting
confidence: 49%
See 2 more Smart Citations
“…We found the effects of sex and/or reproductive allocation on spring FEC became more apparent in adults compared to juveniles and yearlings: juvenile FEC was not influenced by sex or reproductive status; there was marginal evidence that yearling FEC was influenced by sex; and adult FEC was influenced by both. Juveniles had generally high FEC, as predicted from previous research on other wild vertebrates (Wilson et al 1996;Isomursu et al 2006;Hayward 2013;Watson et al 2016) and humans (Simon et al 2015), which suggests that juveniles have not developed fully effective immune defences. Yearling males tended to have higher spring FEC than females (marginal statistical support; estimate = 0.36 AE 0.17 SE, DAIC = À1; evidence ratio = 0.63); this result is consistent with studies from diverse species that have found males to have less effective immune responses (Tschirren et al 2003;Hayward 2013;Klein & Flanagan 2016;Watson et al 2016).…”
Section: Reproductive Allocation Influences Fecsupporting
confidence: 49%
“…; Hayward ; Watson et al . ) and humans (Simon et al . ), which suggests that juveniles have not developed fully effective immune defences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous analyses have revealed strong positive associations between different antibody isotypes measured in Soay sheep plasma (Nussey et al, ; Watson et al, ) and faeces (Watt et al, ) and have shown that T. circumcincta ‐specific pan‐isotypic antibody contains substantial among‐individual variation (Hayward et al, ). We aimed to build upon this work by estimating the individual‐level variation (repeatability) and individual‐level correlations between antibody measures with multivariate mixed‐effects models in ASReml‐R ver 3.0 (Gilmour, Gogel, Cullis, & Thompson, ) with the dataset of 248 samples from 54 females.…”
Section: Methodsmentioning
confidence: 99%
“…In mammals, age is one intrinsic factor that can alter resistance to infection, because immune processes generally improve from early life to adulthood and then decline in old age (Simon, Hollander, & McMichael, 2015). When young, the cellular immune responses of juveniles typically differ both qualitatively and quantitatively from those of adults (Ramsburg, Tigelaar, Craft, & Hayday, 2003;Watson et al, 2016) and juveniles are less likely to have the acquired immunity that develops following exposure to pathogen antigen than adults, (Cattadori, Boag, Bjørnstad, Cornell, & Hudson, 2005;Ferreira, Torelli, et al, 2019), and thus, juveniles are generally more vulnerable to infection than adults.…”
Section: Introductionmentioning
confidence: 99%